Development of Song-Assisted SiMo Application with TGT Model on Animal Morphology Adaptation Material at Elementary School - Makarima, Safina; Sutikno, Putri Yanuarita (Jurnal Pijar Mipa, 2024)
The development of science has encouraged the birth of various innovative technologies that can facilitate human work in daily life. This symbolizes technological progress in various fields, including education, such as the rampant use of technology-based learning media in a more effective learning process. This study assesses the feasibility, practicality, and effectiveness of using Song-Assisted SiMo Application products with TGT Models on Animal Morphology Adaptation Materials in grade VI of elementary school. Indicators in this study are that it is hoped that students can appropriately determine and analyze the form of morphological adaptation in animals. The research method used is Research and Development (R&D) with the Borg and Gall Model, which includes eight out of ten stages: (1) potential and problems; (2) data collection; (3) product design; (4) design validation; (5) design revision; (6) product trials; (7) product revision; and (8) trial use. The results of the study show that the SiMo Application media is a product that is worth using, with a percentage value of 91.25% from media experts and 93.75% from material experts, and supported by the results of the questionnaire response of 88% of teachers and 91% of students. In the results of the N-gain test, a 64% percentage was obtained, showing that the SiMo Application product effectively improves student learning outcomes.